Risk management on the metals market - Krężołek, Dominik; Trzpiot, Grażyna (Zarządzanie ryzykiem na rynku metali, 2020)
The purpose of this paper is to attempt to classify risk which can be observed when one deals with data from the metals market. Usually the general definition of risk includes two dimensions. The first one is the probability of occurrence and the second one are the associated consequences of a set of hazardous scenarios. In this research the authors try to add a new dimension: the source of risk, which can be defined in terms of the level of turnover (volatility of volume) and price (volatility of returns). One can categorize risks in terms of multidimensional ranking based on a comparative evaluation of the consequences, probability, and source of a given risk. Another dimension is the chosen risk measures, in the meaning of the risk model. In risk analysis, some selected quantile risk measures were proposed: VaR, Expected Shortfall, Median Shortfall and GlueVaR. The empirical part presents a multidimensional risk analysis of the metal market
Econometrics = Ekonometria, 2020, Vol. 24, No. 2, s. 86-97
Keywords: risk measure; modified GlueVaR; extreme risk; sources of risk; metals market; miara ryzyka; zmodyfikowany GlueVaR; ryzyko ekstremalne; źródła ryzyka; rynek metali